Vấn đề con người và chính sách mở cửa - Nguyễn, Văn Thân (2011)
Tác giả: Nguyễn Văn Thân, PGS-PTS; Đặng Bá Lãm, PGS-PTS; Mạc Văn Trang, PGS-PTS; Bùi Thanh Quất, PGS; Nguyễn Quốc Hùng, PGS-PTS; Đỗ Quang Hưng, PGS-PTS; a. ưu Đoàn Huynh; Nguyễn Lạc Thế, PTS; Nguyễn Danh Bình, Thạc sĩ; Lê Xuân Bình, PTS -- Từ khóa: Con người; Chính sách mở cửa; Đảng; Chính sách đối ngoại; Nhà nước